160 High dose octreotide; a novel therapy for the treatment of drug refractory postural orthostatic tachycardia syndrome in patients with joint hypermobility syndrome. (9th June 2011) - French, A E; Shepherd, C; Horne, A; Parker, C; Tagney, J; Pitts-Crick, J; Johnson, T; Thomas, G
Abstract : Introduction: Postural orthostatic tachycardia syndrome (POTS) is defined as symptomatic orthostatic intolerance with an increase in heart rate of 30 beats per minute within 10 min of head up tilt (HUT). This dysautonomia causes wide-ranging symptoms including palpitations, presyncope, chronic fatigue, headache and cognitive difficulties. When POTS occurs in patients with pre-existing Joint Hypermobility Syndrome (JHS), symptoms begin approximately a decade earlier than non-JHS patients with a preponderance of neurological features, secondary to cerebral hypoperfusion. Vascular laxity with splanchnic venous pooling has been implicated as a causative factor thus measures to expand plasma volume (thereby increasing mean arterial pressure and restoring cerebral perfusion) form the mainstay of therapy. Symptomatic improvements have been previously reported in POTS patients with the somatostatin analogue Octreotide, a powerful splanchnic vasoconstrictor. We report the first UK series of JHS patients with drug refractory POTS treated with high-dose octreotide. Methods: Six patients (female, aged 21–52) were referred to our institution. All had known JHS (4 requiring a wheelchair), neurological symptoms (headache and cognitive impairment) and diagnostic tilt-table testing with a mean increase in heart rate of 64 beats/min (range 47–73) with head-up tilt (HUT). All patients had remained symptomatic despite pre-treatment with a mean of 5 POTS medications (range 5–7) including fludrocortisone, midodrine, propranolol, ivabradine, selective serotonin reuptake inhibitors, gabapentin and erythropoietin. Octreotide was commenced using a short-acting preparation given 3 times daily (dosage 50–250 μg according to body mass) in conjunction with a long-acting (monthly), intramuscular injection (dosage 10–30 mg). The short-acting preparation was weaned following the second monthly injection. Results: During follow-up of 3 months (range 1–8), 3 (50%) patients reported a complete resolution of all postural and neurological symptoms which corresponded with a normalised response to HUT. The remaining patients reported a dramatic improvement but ongoing postural symptoms. No patients developed supine hypertension. Side effects including mild abdominal discomfort and transient diarrhoea were reported in 3 (50%) patients. Conclusion: Octreotide is increasingly recognised as an effective therapy in POTS patients. Both short-acting, subcutaneous (0.9 μg/Kg) and long-acting, intramuscular (10–20 mg) preparations have previously been reported. We conclude that higher dosages of both preparations when administered together are effective and well tolerated in JHS patients with drug refractory POTS.